2001
DOI: 10.1111/j.1553-2712.2001.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Institutional Review Board Responses to a Standard Protocol for a Multicenter Clinical Trial

Abstract: Abstract.Multicenter clinical trials require approval by multiple local institutional review boards (IRBs). The Multicenter Airway Research Collaboration mailed a clinical trial protocol to its U.S. investigators and 44 IRBs ultimately reviewed it. Objective: To describe IRB responses to one standard protocol and thereby gain insight into the advantages and disadvantages of local IRB review. Methods: Two surveys were mailed to participants, with telephone follow-up of nonrespondents. Survey 1 was mailed to 82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 35 publications
2
76
0
Order By: Relevance
“…The potential for selection bias in minimal risk, observational research requiring informed consent (Tu et al 2004) and variability in IRB review (Bennett et al 2001;Silverman, Hull, and Sugarman 2001;Stair et al 2001;Hirshon et al 2002) have been previously described. However, there has not been previous research assessing the potential impact of federal research policy (i.e., the Privacy Rule and need for federalwide assurances) on health services research.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for selection bias in minimal risk, observational research requiring informed consent (Tu et al 2004) and variability in IRB review (Bennett et al 2001;Silverman, Hull, and Sugarman 2001;Stair et al 2001;Hirshon et al 2002) have been previously described. However, there has not been previous research assessing the potential impact of federal research policy (i.e., the Privacy Rule and need for federalwide assurances) on health services research.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, all sites gave approval but not without considerable time and effort by both investigators and institutional review board members. Eight studies reported differences in the approach to consent, similar to our experience with the BBOP study (7). In particular, with juvenile subjects, research ethics committees focused on the children's status as vulnerable and expressed concerns about consenting procedures as well as emphasizing the need for children to be protected in research (8).…”
Section: Other Experiencesmentioning
confidence: 88%
“…In addition, a single site might bias the results because IRBs show extreme variability in their initial responses to standard protocols. 26 We need more trials that cover all types of trials planned regardless of time (eg, all early protocols) and locations (eg, university, general hospital, research institute). Second, participants were not randomized; hence, we could not simply compare early and rejected protocols.…”
Section: Limitationsmentioning
confidence: 99%